Analisis Status Gizi Balita di Puskesmas Bojong Rawalumbu Kota Bekasi - Syaiful Mizan; Puput Oktamianti; Alvia Soliah (Syntax Literate, 2023)
The purpose of this study was to determine the nutritional status of toddlers at the Bojong Rawalumbu Health Center, Bekasi City. This type of descriptive research with cross sectional design. The sample used was 3,757 children aged 0-59 months who had weight and height records in the working area of the Bojong Rawalumbu Health Center, Bekasi City. The data collection technique uses total sampling from secondary data taken in August 2022. Data analysis uses univariate which is presented in the form of a frequency distribution table. It was found that the majority of respondents aged >12-36 months were 1,663 respondents (44.3%) with good nutritional status 1,385 respondents (36.9%), aged >36-59 months with poor nutrition 6 respondents (0.2%); the average male gender with good nutrition is 1,607 respondents (42.8%) and 10 respondents (0.3%) with severe malnutrition; The average weight of toddlers > 10-20 kg with good nutritional status was 1,735 respondents (46.2%) and severe nutrition with a weight of 1-10 kg there were 14 respondents (0.4%); while the average toddler with TB 40-100 cm with good nutrition there are 2,664 respondents (70.9%) and severe nutrition 15 respondents (0.4%). The nutritional status of toddlers in the working area of the Bojong Rawalumbu Health Center, Bekasi City, found that 3,085 respondents (82.1%) had good nutritional status, 16 respondents (0.5%) were severely malnourished, 109 respondents (2.9%) were undernourished, 109 respondents (2.9%) were at risk of malnutrition. more 342 respondents (9.1%), over nutrition 134 respondents (3.6%) and obese 69 respondents (1.8%). For respondents and their families to increase knowledge about the nutritional status of toddlers from various media.